Techniques adopted in teaching students organic chemistry course for several years - Sukmawati, Wati (Jurnal Inovasi Pendidikan IPA, 2020)
Organic chemistry is a compulsory course for both science and science education students. Therefore a proper course design is needed to ease the understanding of the concepts considered difficult in terms of learning activities, application of technology, and innovation in the curriculum structure. Various studies have been carried out to solve problems in organic chemistry courses, with the majority focused on concept mastery due to students’ difficulty. Furthermore, their thinking skills need to be improved after graduating from the university in accordance with the 21st century, which is associated with the application of technology and curriculum modification. The results showed that most studies in organic chemistry courses focused on improving students’ concept, understanding, and thinking abilities. Therefore, little application of technology and curriculum modification is still needed in the innovation of organic chemistry courses, especially in applying technology. In conclusion, courses related to organic chemistry still need innovation, especially in the application of technology. This research can serve as a reference for developing organic chemistry learning in the future.